PRODUCTION OF BITUMEN FROM OILY WASTE - Бадриддинова Ф. М.; Хабибуллаева Р. М.; Хайруллаева Д. Х.; Махкамова Л. К. (Web of Journals Publishing, 2024)
In order to create environmentally friendly low-waste technologies for the disposal of oil sludge, a technology has been developed for their processing by its vacuum distillation and oxidation to obtain an oxidized secondary product similar in characteristics to standard road bitumen.
Keywords: oil sludge, tar, vacuum distillation, oxidation, oxidized road bitumen.